Classifying dengue: a review of the difficulties in using the WHO case classification for dengue haemorrhagic fever - Bandyopadhyay, S.; Lum, L.C.; Kroeger, A. (2006)
BACKGROUND: The current World Health Organisation (WHO) classification of dengue includes two distinct entities: dengue fever (DF) and dengue haemorrhagic fever (DHF)/dengue shock syndrome; it is largely based on pediatric cases in Southeast Asia. Dengue has extended to different tropical areas and older age groups. Variations from the original description of dengue manifestations are being reported.